TOWARD OPTIMUM SYNERGY OF MONETARY POLICY IN DUAL FINANCIAL/BANKING SYSTEM - Ascarya, Ascarya (Journal of Indonesian Economy and Business, 2009)
In a country adopting dual financial/banking system, where a conventional financial system coexists with an Islamic financial system, monetary authority has the responsibility to maintain financial/monetary stability and synergy of both systems. This study analyses and compares one of the main pillars of conventional monetary system and Islamic monetary system (i.e., interest system vs. profit-and-loss sharing/PLS system) and try to come up with the possible conduct of optimum monetary policy under dual financial/banking system. The results show that PLS system is superior to interest system in fairness, justice, efficiency, and stability. Therefore, the optimum synergy in the dual financial/banking system can be achieved when monetary policy in conventional systembenchmarks its policy rate to the PLS market return in Islamic financial market of Islamic system, which will ensure optimum market efficiency that maximize distributive social welfare and justice. Monetary policy in managing money supply is only a response to thedynamic activity in the real sector. While, active monetary policy can be conducted, not by altering M, but by altering V, i.e. to increase the flow of money in the economy by issuing central bank SUKUK with PLS market return to finance government projects, commercially as well as socially, in the real sector.Keywords: Islamic Monetary System, Islamic Financial System, Dual Banking Financial System